2006
DOI: 10.1007/s11270-006-3113-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Total Mercury and Monomethylmercury in the Earthworm Eisenia Fetida

Abstract: Standard Form 298 (Rev. 8/98) REPORT DOCUMENTATION PAGEPrescribed by ANSI Std. Z39.18 Form Approved OMB No. 0704-0188The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 33 publications
5
24
2
Order By: Relevance
“…To the best of our knowledge, there are few works dealing with mercury bioaccumulation kinetics; however, in the literature, some cases of bivalves, like Chlamys varia (Metian et al 2009) and Corbicula fluminea (Inza et al 1998), showed a linear pattern of mercury accumulation (through a solution pathway), which is in accordance with the present results. For polychaetes, no references regarding mercury bioaccumulation kinetics were found; only some studies performed with earthworms (Burton et al 2005) also revealed a linear pattern of bioaccumulation of total mercury.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are few works dealing with mercury bioaccumulation kinetics; however, in the literature, some cases of bivalves, like Chlamys varia (Metian et al 2009) and Corbicula fluminea (Inza et al 1998), showed a linear pattern of mercury accumulation (through a solution pathway), which is in accordance with the present results. For polychaetes, no references regarding mercury bioaccumulation kinetics were found; only some studies performed with earthworms (Burton et al 2005) also revealed a linear pattern of bioaccumulation of total mercury.…”
Section: Discussionmentioning
confidence: 99%
“…However, total mercury in soils also affected the bioaccumulation factors. The bioaccumulation factor for earthworm to both total mercury and methylmercury became larger in the lower contaminated soils and became smaller in the higher mercury contaminated soils (Burton et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…However, Zhang et al (2009) mercury in earthworms decreased with earthworm body length due to the growth dilution. Many factors affecting mercury bioaccumulation (BF), including mercury species, and the size and species of earthworms, existence of organic acids such as tannic acid, humic and fulvic acids and so on (Burton et al, 2006;Veiga, 2008, 2009;Zhang et al, 2009). In general, humic and fulvic acid and tannic acid increased bioaccumulation of mercury in earthworms due to the increase in dissolution of mercury from minerals or tailings Veiga, 2008, 2009).…”
Section: Bioavailability Of Mercury In Floodplain Soils To Native Earmentioning
confidence: 99%
See 2 more Smart Citations